A Preliminary Model of the Wrist Midcarpal Joint - Pendola, Martin; Petchprapa, Catherine; Wollstein, Ronit (Journal of Wrist Surgery, 2021)
Background A challenge to deciphering the effect of structure on function in the wrist involves difficulty in obtaining in-vivo information. To provide a platform to study wrist mechanics using in vivo acquired forces, we developed a model of the midcarpal joint based on computed tomography (CT) scans of normal wrists. Finite element analysis (FEA) can enable application of in vivo collected information to an ex vivo model.Objectives The objectives of this study are to (1) create a three-dimensional model of the midcarpal joint of the wrist based on CT scans and (2) generate separate models for the midcarpal joint based on two distinct wrist types and perform a pilot loading of the model.Methods CT scans from a normal patient database were converted to three-dimensional standard template library (STL) files using OsiriX software. Five type 1 and five type 2 wrists were used for modeling. A simulated load was applied to the carpometacarpal joints in a distal-to-proximal direction, and FEA was used to predict force transfer in the wrist.Results There were 33% type 1 and 67% type 2 wrists. The midcarpal joint dimensional measurements estimated from the model had intermediate agreement between wrist type as measured on CT scan and as predicted by the model: 56% Cohen's kappa (95% confidence interval) = 0.221 (0.05–0.5). Surface stress on the carpometacarpal joints is different in type 1 and type 2 wrists. On loading the neutral wrist, the capitolunate angle was 90 degrees in type 1 wrists and 107 degrees in type 2 wrists (p < 0.0001).Conclusions The model predicted differences in movement and force transfer through the midcarpal joint dependent on structural type. This knowledge can improve our understanding of the development of disparate patterns of degeneration in the wrist.
Keywords: arthritis; lunate type; midcarpal joint; model; wrist